Visual Impairment Due to Bilateral Multifocal Choroidal Metastasis of Parotid Adenocarcinoma: A Case Report - Walls, Gerard; Napier, Seamus; Stewart, David (Frontiers in Oncology, 2014)
Background Orbital metastases are an uncommon finding, being present in just 9% deceased patients with metastatic cancer. Only a quarter of patients with choroidal metastases have bilateral disease. Parotid cancer is not a common form of head and neck malignancy. Bilateral multifocal metastases from adenocarcinoma ex pleomorphic of parotid gland have been documented just once before in the literature. We present a similar case where palliative EBRT was used to gain local control with minimal toxicity. Case Presentation The case of a 45 year old Caucasian gentleman who presented to his general practitioner with otalgia and weight loss. Imaging revealed a mass in the deep lobe of the left parotid gland, invading into the medial pterygoid muscle. PET-CT revealed locoregional and distant lymphatic involvement plus disseminated skeletal metastases. Lymph node examination revealed adenocarcinoma ex pleomorphic histology. Within weeks of this diagnosis, the patient developed rapidly progressive visual impairment. Ophthalmologists found multifocal uveal masses bilaterally. Palliative fractions of external beam radiotherapy were delivered to the orbits before combination chemotherapy. We discuss the patient's presentation, histopathology and management, with support from the literature regarding applied and related therapies. Summary In this rare presentation of disseminated malignancy affecting the choroid bilaterally, the authors demonstrate the application of palliative EBRT to good local effect. Given the nature of this treatment and that of the metastases, in the setting of incurable disease orbital morbidity is likely to occur again before the patient's death. Awareness of the initial symptoms is important to provide prompt care and maintain quality of life.